Bacteremia associated with Enterobacter sakazakii (yellow, pigmented Enterobacter cloacae). - Monroe, P W (1979)
A case report of bacteremia due to Enterobacter sakazakii, listed previously as yellow-pigmented Enterobacter cloacae (R. Sakazaki, in R. E. Buchanan and N. E. Gibbons, ed., Bergey's Manual of Determinative Bacteriology, 8th ed., p. 325, 1974), occurred in a 7-day-old, Caucasian male who responded successfully to ampicillin therapy. The source of the infection was not known; however, because of the time lapse between birth and the onset of symptoms, the infection was thought to have occurred postnatally.